Evaluation of Risk Factors for Development of Pulmonary Hypertension in Patients with End Stage Renal Disease Undergoing Hemodialysis - Hussein Fadhil, Ali; Mahdi Hashim, Hashim; Sami Malik, Arif; Kadhum Manuti, Jawad; Basheer Hamid , Moayed (Diyala Journal of Medicine, 2023)
Background: Pulmonary arterial hypertension (PAH) has recently been identified as a common complication in patients with end-stage renal disease (ESRD) who are undergoing hemodialysis (HD) or peritoneal dialysis (PD). The risk factors for the development of PAH in those patients are not well understood. Objective: To investigate the risk factors for the development of PAH in patients with ESRD on HD. Patients and Methods: This is a hospital-based cross-sectional study of 50 ESRD patients undergoing HD. The pulmonary artery systolic pressure (PASP) was measured using echocardiography. PASP ˃ 25 mmHg at rest was defined as PAH. As a result, patients were divided into two groups: those who had PAH and those who did not. Each patient's demographic, biochemical, and echographic findings were documented. Results: Out of 50 patients, 19 (38%) had PAH, while the remaining 31 (62%) had normal PASP. In multivariate analysis, HD duration > 3.4 years (OR= 2.13, 95%CI=1.45-31.38, p= 0.025), hypertension as a cause of ESRD (OR=6.12, 95%CI=1.4-26.77, p=0.031), hemoglobin (Hb) ≤ 10.0 g/dl (OR= 4.35, 95%CI=1.88-9.84, p= 0.018), and left ventricular ejection fraction (LVEF)≤ 55% (OR= 6.75, 95%CI=1.87-23.74, p=0.021) were independent factors associated with PAH. PASP had a significant positive correlation with the rate of fistula flow (r= 0.295, p= 0.038) and E/A ratio (r= 0.368, p= 0.008), but a significant negative correlation with LVEF (r= -0.345, p= 0.014). PASP had a positive significant correlation with each of rate of fistula flow (r= 0.295, p= 0.038) and E/A ratio (r= 0.368, p= 0.008), while it has a negative significant correlation with LVEF (r= -0.345, p= 0.014). Conclusion: Longer duration of HD, hypertensive nephropathy as a cause of ESRD, Hb≤ 10 g/dl, and LVEF ≤55% are among the demographic, biochemical, and clinical factors associated with the development of PAH in patients with ESRD under HD. The PASP has a positive correlation with fistula flow rate and E/A ratio and a negative correlation with LVEF.